2020
DOI: 10.1016/j.jclepro.2019.119378
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on influence of antimony tin oxide/silver nanofluid on direct absorption parabolic solar collector

Abstract: This paper discusses the synthesis and characterization of a novel hybrid nanofluid and its performance analysis on a parabolic trough direct absorption solar collector. Broadening the absorption spectra of working fluid using nanoparticles is the new research revolution for increasing the volumetric solar absorption efficiency. It is reported that plasmonic silver nanoparticles have higher absorption in visible spectra while antimony doped tin oxide has an absorption peak in the near-infrared region. Hence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…In particular, studies have focused on four-wave interactions and the self-action of light waves [ 7 , 8 , 9 , 10 ]. Without detailed knowledge of the optical properties of nanofluids, it is impossible to create next-generation solar collectors [ 11 , 12 , 13 , 14 , 15 ]. For example, [ 16 ] summarized the results of studies on the nanocolloids of ionic liquids (i.e., ionic liquids with nanoparticles in suspension), which can be directly applied to convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have focused on four-wave interactions and the self-action of light waves [ 7 , 8 , 9 , 10 ]. Without detailed knowledge of the optical properties of nanofluids, it is impossible to create next-generation solar collectors [ 11 , 12 , 13 , 14 , 15 ]. For example, [ 16 ] summarized the results of studies on the nanocolloids of ionic liquids (i.e., ionic liquids with nanoparticles in suspension), which can be directly applied to convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Further, many researchers have focused on the experimental determination or simulation of the optical properties of Ag morphologies for the application of plasmonic nanoparticles to solar applications. [45][46][47] Recently, a novel DASC concept based on "Rayleigh-Bénard convection" was introduced and tested under solar simulator conditions considering ZrC and TiN based dispersion in base fluids like water and synthetic oils. 48,49 For practical applications of such concepts, reverse illumination could be achieved by using reflective surfaces, eliminating the need of additional energy and tracking mechanism.…”
Section: Nano-fluid Laden Direct Absorption Solar Collectormentioning
confidence: 99%
“…Qin et al 44 suggested that four‐edge star shape Ag nanoparticles could achieve a broad absorption curve on solar spectrum. Further, many researchers have focused on the experimental determination or simulation of the optical properties of Ag morphologies for the application of plasmonic nanoparticles to solar applications 45–47 …”
Section: Introductionmentioning
confidence: 99%
“…ATO (Antimony Tin Oxide) nanofluid is very suitable for these requirements. Many researchers have studied its characteristics [25,26] which could provide reference for this study. There are many literatures about the preparation method and spectral characteristics of ATO nanofluid.…”
Section: Selection Of Nanofluidsmentioning
confidence: 99%